Design and Implementation of a Microstrip Patch Antenna Using ADS Software - Milad Albagul; Roberto Quaglia; Aleksander Bogusz; Abdulgani Albagul (African Journal of Advanced Pure and Applied Sciences, 2024)
In this paper, the design of a microstrip patch antenna using EMPro simulation is curried out to obtain a specific coefficient reflection at 3.6 GHz and to observe the gain and radiation pattern in 2D and 3D for both infinite ground plane and finite ground plane is investigated. A microstrip antenna consists of conducting patch on a ground plane separated by dielectric substrate. The micro strip antennas are the present-day antenna designer’s choice. Low dielectric constant substrates are generally preferred for maximum radiation. In this paper, we will study the rectangular microstrip patch antenna in terms of coefficient reflection, gain and radiation for the infinite ground plane and the finite ground plane. An explanation of each step will be made with the support of the theoretical concept. The results show the radiation pattern major lobe in the z-direction with no minor lobes for the infinite ground plane, whereas for the finite ground plane shows the major lobe in the z-direction with minor lobes in other directions.